Emerging sensor-cloud technology for pervasive services and applications - Hassan, Mohammad Mehedi; Pathan, Al-Sakib Khan; Huh, Eui-Nam; Abawajy, Jemal (SAGE Publications Inc., 2014)
This is an Editorial article for the Special Issue on "Emerging Sensor-Cloud Technology for Pervasive Services and Applications" of the International Journal of Distributed Sensor Networks.